Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Harga Terhadap Kepuasan Konsumen - Nuke Dyah Pangesti; Henry Casandra Gultom; Mochamad Fadjar Dharmaputra (MANAJEMEN, 2026)
This study aims to empirically test the effect of product quality, service quality, and price on customer satisfaction at the Fatmawati branch of Optik B Riski Semarang. The study population was all customers who made purchases, with a sample of 120 respondents determined using a purposive sampling technique. Data were collected through a questionnaire and analyzed using IBM SPSS 27.0, including validity and reliability tests, classical assumption tests, multiple regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that product quality, service quality, and price have a positive and significant effect on customer satisfaction, both partially and simultaneously. The coefficient of determination indicates that the independent variables are able to explain customer satisfaction, while the remaining 46.5% is influenced by other variables outside this study.